2019
DOI: 10.1111/jpn.13093
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal microbiota of broilers submitted to feeding restriction and its relationship to hepatic metabolism and fat mass: Fast‐growing strain

Abstract: The present study was conducted to verify how feed restriction affects gut microbiota and gene hepatic expression in broiler chickens and how these variables are related to body weight gain. For the experiment, 21‐d‐old Cobb500TM birds were distributed in a completely randomized experimental design with three treatments: T1. Control (ad libitum—3.176 Mcal/kg ME—metabolizable energy—and 19% CP—crude protein); T2. Energetic restriction (2.224 Mcal/kg ME and 19% CP) from 22 to 42 days with consumption equivalent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 38 publications
1
9
0
Order By: Relevance
“…Interaction between feed withdrawal and feed additive Progut® were not significantly difference in total micro flora counts and some enzymes of broiler chicks. Our results agree partially with Lunedo, et al [46] who found that used feed restriction on broiler chicks reduced Enterococcus and Enter bacteriaceae enhanced Lactobacillus counts. Shafiei, et al [26] found that used feed withdrawal time at 8, 10 hours/day had not effected on E. coli count however, Lactobacilli count was enhanced by exposed broiler chicks 12 h feed withdrawal.…”
Section: Total Micro Flora Counts and Some Enzymessupporting
confidence: 93%
“…Interaction between feed withdrawal and feed additive Progut® were not significantly difference in total micro flora counts and some enzymes of broiler chicks. Our results agree partially with Lunedo, et al [46] who found that used feed restriction on broiler chicks reduced Enterococcus and Enter bacteriaceae enhanced Lactobacillus counts. Shafiei, et al [26] found that used feed withdrawal time at 8, 10 hours/day had not effected on E. coli count however, Lactobacilli count was enhanced by exposed broiler chicks 12 h feed withdrawal.…”
Section: Total Micro Flora Counts and Some Enzymessupporting
confidence: 93%
“…The cecum contains majority of the intestinal flora and plays a key role in the digestion and absorption process of poultry ( 57 ). Some studies have shown that changes in the intestinal flora can affect intestinal health ( 58 ), and the cecal microbiota composition significantly impacts the growth and health of poultry ( 59 , 60 ). A study found that the addition of Clostridium butyricum to the feeds of early Muscovy ducks improved the cecal microflora richness ( 61 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, inconsistent data have been published on growth parameters. Previous studies confirmed compensatory growth following FR in chickens (Tumova et al 2002;van der Klein et al 2017;Lunedo et al 2019), rabbits (Tumova et al 2002;Gidenne et al 2012;Crespo et al 2020), and nutrias (Tumova et al 2021a). However, other studies reported growth retardation due to FR in chickens (Tumova and Chodova 2018;Gratta et al 2019), rabbits , turkeys (Tumova et al 2002), lambs (Santos et al 2018), and pigs (Carco et al 2018).…”
mentioning
confidence: 73%
“…https://doi.org/10.17221/185/2021-CJAS broiler chickens (Mohammadalipour et al 2017;Tumova et al 2019), rabbits (Gidenne et al 2012;Birolo et al 2016), andpigs (Le Floc'h et al 2014). It was reported that FR resulted in a similar or better feed conversion ratio in several species, including broiler chickens (van der Klein et al 2017;Tumova and Chodova 2018;Lunedo et al 2019), rabbits (Gidenne et al 2012;Chodova et al 2019;Crespo et al 2020), and turkeys (Tumova et al 2002). However, inconsistent data have been published on growth parameters.…”
mentioning
confidence: 99%